If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7y + -2x + -6 = 0 Reorder the terms: -6 + -2x + 7y = 0 Solving -6 + -2x + 7y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + -2x + 6 + 7y = 0 + 6 Reorder the terms: -6 + 6 + -2x + 7y = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -2x + 7y = 0 + 6 -2x + 7y = 0 + 6 Combine like terms: 0 + 6 = 6 -2x + 7y = 6 Add '-7y' to each side of the equation. -2x + 7y + -7y = 6 + -7y Combine like terms: 7y + -7y = 0 -2x + 0 = 6 + -7y -2x = 6 + -7y Divide each side by '-2'. x = -3 + 3.5y Simplifying x = -3 + 3.5y
| 3(x+2)+2x=2(x+3)+3x | | 8-3(6z+4)=2(-6z-7)+5 | | what+8=9 | | 7x-2y+6=0fory | | 5x(4x^3+x-7)= | | 2004=1/2p | | 2x=(370/4) | | 63=1/3n | | 2x^2+5x-8x=0 | | 7x-3/5=1/3 | | 2x*(360/4) | | 5x+6(4-x)=23 | | z-3.3z+2.6=-2.8(z+3) | | c=50m+30 | | -x^2+11x+26=0 | | 3(2+2x)=24 | | 5(x-6)+4=(x+2)-4 | | -2.1(y+1)=-0.6(y+1.5) | | 0.7xY=1000000 | | 0.6x+2.9=4.9 | | 3x-x^2=18 | | -12z+28=-4(3z-7) | | (7x^1/2)(2x^1/4) | | (7x^1/4)(2x1/4) | | sin^2x+sinx=1 | | logn;[5;[[1]/[25]]] | | -3+4=-28 | | -3+4=28 | | (24m^6p^2)/(6m^8p) | | 6g+7=-14+7 | | 9x^2-y^2=80 | | -14=s/12 |